Response to vitamin D replacement in overweight and normal weight children with vitamin D deficiency - In Hyuk Chung; Yu Sun Kang; Eun-Gyong Yoo (Korean Society of Pediatric Endocrinology, 2019)
Purpose It is well known that obesity is related to vitamin D deficiency (VDD). We investigated the response to vitamin D replacement in normal-weight and overweight children. Methods This was a prospective study including 62 Korean children with VDD. VDD was defined as a serum 25-hydroxycholecalciferol (25(OH)D) concentration <20 ng/mL. Overweight was defined as a body mass index (BMI)≥the 85th percentile (n=21), and normal weight as a BMI between the 5th and 84th percentiles (n=41). All participants received vitamin D3 supplementation (2,000 IU/day) for 8 weeks. The serum levels of 25(OH)D, PTH and biochemical parameters were measured before and after treatment. Results The mean age was 10.0±1.4 years in normal-weight children and 10.0±2.1 years in overweight children (P=0.93). After 8 weeks of treatment, 61.9% of normal-weight children and 47.6% of overweight children achieved vitamin D sufficiency (P =0.30). The mean serum 25(OH)D levels after vitamin D replacement were 33.8±7.6 ng/mL and 30.3±6.6 ng/mL in normal-weight and overweight children, respectively (P =0.10). The mean calcium/creatinine ratios after treatment were 0.09±0.07 and 0.08±0.06 in the normal-weight and overweight groups, respectively, and no hypercalciuria was found. In multiple regression analysis, the response to vitamin D replacement was influenced by the BMI (β=-1.0, P=0.03) and sex (β=-4.0, P=0.04). Conclusions Eight weeks of vitamin D replacement (2,000 IU/day) is sufficient to overcome vitamin D deficiency in normal-weight and overweight children without any complications.